Effects of metal exposure on motor neuron development, neuromasts and the escape response of zebrafish embryos - Sonnack, Laura; Erdinger, Lothar; Henny, Nicole (Neurotoxicology and teratology, 2015)
Low level metal contaminations are a prevalent issue with often unknown consequences for health and the environment. Effect-based, multifactorial test systems with zebrafish embryos to assess in particular developmental toxicity are beneficial but rarely used in this context. We therefore exposed wild-type embryos to the metals copper (CuSO4), cadmium (CdCl2) and cobalt (CoSO4) for 72 h to determine lethal as well as sublethal morphological effects. Motor neuron damage was investigated by immunofluorescence staining of primary motor neurons (PMNs) and secondary motor neurons (SMNs). In vivo stainings using the vital dye DASPEI were used to quantify neuromast development and damage. The consequences of metal toxicity were also assessed functionally, by testing fish behavior following tactile stimulation. The median effective concentration (EC50) values for morphological effects 72 h post fertilization (hpf) were 14.6 mg/L for cadmium and 0.018 mg/L for copper, whereas embryos exposed up to 45.8 mg/L cobalt showed no morphological effects. All three metals caused a concentration-dependent reduction in the numbers of normal PMNs and SMNs, and in the fluorescence intensity of neuromasts. The results for motor neuron damage and behavior were coincident for all three metals. Even the lowest metal concentrations (cadmium 2 mg/L, copper 0.01 mg/L and cobalt 0.8 mg/L) resulted in neuromast damage. The results demonstrate that the neuromast cells were more sensitive to metal exposure than morphological traits or the response to tactile stimulation and motor neuron damage.